Reconnecting Ancestral Wisdom and Sustainability Environmental Health Education: A Qualitative Study of Eco-Literacy and Cultural Transformation in Indonesian Primary Schools - Vindi Tyastutik; Anggun Wida Prawira; Aqila Lintang Qatrunnada; Afiqah Lituhayu Izzatunnisa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study examines how integrating local ecological wisdom and eco-literacy education fosters environmental awareness, behavioral transformation, and health outcomes among Indonesian primary school students. The research responds to the ecological paradox of rapid technological growth amid worsening environmental degradation, where youth eco-literacy remains below 45%, indicating a gap between environmental knowledge and sustainable action. The study aims to develop a culturally responsive model of sustainability education that connects environmental ethics, cultural identity, and public health. Using a qualitative case study design, the research was conducted at SD Islam Kreatif Mutiara Anak Sholeh, Sidoarjo, East Java, from July to August 2025, involving 60 students and six teachers. Data were collected through semi-structured interviews, observations, and document analysis. Four major themes emerged: (1) cultural narratives as catalysts for environmental awareness, (2) eco-literacy as experiential and behavioral transformation, (3) collaborative learning as collective environmental agency, and (4) eco-health as psychosocial and physical well-being. Findings show that integrating Majapahit-era ecological values and local storytelling into eco-brick and composting projects enhanced students’ responsibility, cooperation, and emotional balance. The study synthesizes Eco-pedagogy, Constructivism, and Eco-health frameworks into a Culturally Responsive Eco-Health Pedagogy, demonstrating that sustainability learning rooted in culture and participation promotes both environmental and health outcomes. This model contributes to the global Education for Sustainable Development (ESD) 2030 agenda by linking culture, ecology, and well-being in primary education.